Improving The Methodology For Developing Future Engineers' Competencies In Computer Modeling - Akhadova K.S. (Genius Journals, 2025)
The article examines the theoretical and methodological foundations for improving the process of developing computer modeling competencies among future engineers in the context of digital education. It analyzes the pedagogical conditions, structural components, and stages of competency formation through an integrative approach combining technical disciplines, digital tools, design thinking, Computer-supported collaborative learning, project-based learning. The research emphasizes the importance of interactive modeling environments, simulation technologies, and interdisciplinary integration in enhancing students’ analytical, creative, and problem-solving skills. The proposed methodology aims to strengthen engineering education by linking theoretical knowledge with practical modeling experience, ultimately fostering innovation-oriented specialists.
Keywords: computer modeling; engineering education; digital technologies